Beyondsoft Co., Ltd. (A) - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
After reviewing the company's results for FY-2009, Ben Wang, CEO of Beyondsoft Co., Ltd. gave a satisfied look out the window at a typically smoggy Beijing skyline. A year that had begun with much uncertainty had ended with a 5% increase in sales and a 35% increase in profits. With the potential for an even more prosperous year ahead, however, he faced both new and familiar challenges. Financing, product strategy and control incentives were just a few topics he needed to review with two of his founding partners, Qiang Ma, now Chief Operating Officer (COO), and Roger Zhang, Chief Technology Officer (CTO), at dinner that night. This case study discusses these issues.